Boko Haram : an African insurgency - Kristensen, Klaus Stig (Department of Political Studies, 2016)
Boko Haram emerged as an independent group in Nigeria in the early 2000s and has since begun an insurgency, primarily operating in the northeastern region of Nigeria and increasingly further south and across the country's borders. Researchers have conducted numerous studies analyzing the causes of the insurgency. However few have compared it to other insurgencies in Nigeria or Africa. This thesis analyzes the causes behind Boko Haram's operations by drawing on the main debates within the literature on causes of insurgency in Africa. This analysis demonstrates how the academic literature on insurgency in Africa highlights important causes of Boko Haram's insurgency, but it also identifies gaps in the literature. One of the most important findings of the thesis is that religion can be a dominate cause of conflict. I argue that one of the main causes of Boko Haram's insurgency is the political competition over various issues between Nigerian Islamic organizations and political organizations. The most recent examples are the implementation of Sharia law across many of the states in northern Nigeria coupled with elite mobilization of youth groups affiliated with mosques. The role of religion as a cause of Boko Haram´s insurgency should not however be exaggerated as specific state weaknesses, especially a weak security apparatus, caused by democratization have also been one of the significant causes.